Double π‐Extended Undecabenzo[7]helicene. Issue 14 (26th February 2021) - Chen, Ying; Lin, Chaojun; Luo, Zhixing; Yin, Zhibo; Shi, Haonan; Zhu, Yanpeng; Wang, Jiaobing
Abstract: This work reports the first double π‐extended undecabenzo[7]helicene 1, which is a large chiral nanographene, composed of 65 fused rings and 186 conjugated carbon atoms. The molecular identity of 1 has been confirmed by single crystal X‐ray diffraction. A wine coloured solution of 1 in dichloromethane absorbs light from ultraviolet to the near infrared, featuring an extremely large molar absorption coefficient of 844 000 M −1  cm −1 at 573 nm. Optically pure 1 shows a record high electronic circular dichroism intensity in the visible spectral range (|Δ ϵ |=1375 M −1  cm −1 at 430 nm) known for any discrete polycyclic aromatic hydrocarbon. These unusual photophysical properties of 1 contrast sharply with those of a mono‐undecabenzo[7]helicene derivative 2 . Abstract : More than double: This paper presents the first double π‐extended undecabenzo[7]helicene. It is a chiral nanographene, displaying an extremely strong light absorption capability with a record high ECD intensity in the visible spectral range known for any discrete PAH compound.